ANALISIS EFEKTIVITAS SISTEM AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (SAKIP) PADA PERWAKILAN BPKP PROVINSI SUMATERA BARAT - Wina Stephani; Efa Yonnedi (Journal Publicuho, 2024)
This research aims to (1) determine the achievements and alignment of the SAKIP components of the West Sumatra Province BPKP Representative, (2) determine the effectiveness of SAKIP implementation including the use of information technology in measuring SAKIP, and (3) determine the factors that influence the implementation of SAKIP in the West Sumatra Province BPKP Representative. The research methodology used is qualitative research with a descriptive approach. Data collection is done through interviews, observation, documentation, and literature study. Interviews were conducted with the leadership and several employees involved in implementing SAKIP. The results of the research show that the achievements of the SAKIP Representative of the BPKP of West Sumatra Province during 2021-2023 experienced fluctuations in increases and decreases. SAKIP at the West Sumatra Province BPKP Representative is running effectively if viewed from 3 (three) effectiveness perspectives according to Duncan's theory. However, there are still obstacles that influence the implementation of SAKIP, namely the reward and punishment system is not yet operational, and the quality of human resources is not optimal because only a small number of employees receive training related to SAKIP and performance accountability.